PENGARUH NILAI PER, PBV DAN ROE TERHADAP KEPUTUSAN INVESTASI SAHAM PADA SEKTOR PERBANKAN - Aditya Ramadhan Indracahya (CV. ADIBA AISHA AMIRA, 2023)
The deed drawn up . Investment decision is one of the decisions made by the company to maximize shareholder wealth. A number of factors are worth analyzing to identify the main factors influencing investment decisions. The determinants of investment are Price Earning Ratio (PER), Price To Book Value (PBV), and Return On Equity (ROE). This study aims to determine the effect of PER, PBV and ROE values on stock investment decisions in the banking sector listed on the Indonesia Stock Exchange for the period 2017 to 2021. This research uses statistical quantitative methods and uses secondary data from the financial reports of related companies. The results of this study is escpected to be able to indicate that the Price Earning Ratio (PER), Price to Book Value (PBV), and Return On Equity (ROE) partially and simultaneously have a significant effect on the Average Return in making stock investment decisions